Meningkatkan Kesadaran Lingkungan : Program Pengelolaan Sampah di SD Negeri Ringinanom 1 - Sekar Kinasih; Ariella Yoharin Panjaitan; Hani'ah Asangadah; Susanti Malasari (Lembaga Pengembangan Kinerja Dosen, 2025)
The waste management program at SD Negeri Ringinanom 1, Magelang Regency, is part of the Student Work Program of Team II, Kuliah Kerja Nyata (KKN) in Ringinanom Village, Universitas Tidar. This program aims to raise environmental awareness from an early age through education and hands-on practice. It includes waste management socialization, the creation of collages from plastic waste, and the production of hydroponic pots using used gallons and bottles. The activities were carried out in stages, starting with a site survey on January 7, 2025, followed by socialization on January 10, 2025, and the practical creation of collages and hydroponic pots on January 16, 2025. This program involved students from classes 4B, 5B, and 6B through interactive socialization, demonstrations, and direct practice. The results showed an improvement in students' understanding of waste management and their skills in processing waste into valuable products. Additionally, the program supports the school’s status as a Sekolah Adiwiyata and aligns with the Projek Penguatan Profil Pelajar Pancasila (P5) curriculum, instilling sustainability values and environmental responsibility from an early age.